Benzothiazole-based Schiff bases as novel AIE(E)gens: Mechanistic insights into distinction between dimethylphenylamine and triphenylamine fragments in double bond-bridged D-A system. (December 2022) - Yang, Rui-Xue; Gong, Shan-Shan; Chen, Li-Li; Peng, Xiao-Chong; You, Xiu-Li; Shi, Rongwei; Sun, Qi
Abstract: Excited-state torsional motions around single or double bond are crucial to the photophysical properties of double bond-bridged diaryl systems. However, the correlations between specific electronic and geometric setup and different types of photo-induced torsional motions remain elusive. In this article, five D-π-A type benzothiazole-based Schiff bases (BAMI-1 −5 ) were synthesized and identified as AIE(E)gens with solid-state fluorescence quantum yields up to 76.5%. Detailed electronic structure/hole-electron analysis and potential energy curve scanning illustrate that electron-donating aniline fragments with different types of N -substituents such as dimethyl (BAMI-1 ) and diphenyl (BAMI-2 ) exert distinctive effects on their excitation and decay processes. In addition, crystallographic and computational results imply that the major factors for the redshifted AIE of BAMI Schiff bases may also be different and depend on their specific structures and excitation characters. Graphical abstract: Image 1 Highlights: Five benzothiazole-based Schiff bases were obtained as AIE(E)gens. N -Substituents of aniline exert distinctive effects on their excitation and decay. Major factors for the redshifted AIE of these Schiff bases are different.